SHARED INSTRUCTIONAL MANAGEMENT IN BILINGUAL EDUCATION - Galicha, Josephine Plan (PEOPLE: International Journal of Social Sciences, 2016)
Addressing the need for relevant and meaningful teaching of English as a Second or Foreign Language in the 21st Century, a bilingual education program catering to Asian ESL learners, in particular, Koreans and Chinese, was the thrust of the research. Using the qualitative approach, areas of response, content, process, support, behavior, validation, credit, and acknowledgment were delved into for assessment. How these matters of immediate concern in a language academy are seriously taken and actualized were the focus in the study. Significant results produced are challenging enough for further research undertakings on educational management. The Shared Instructional Management (SIM) adopted by the administration and the teaching staff makes the present set-up attuned to bi-literacy, specific to Asians, using English, the acknowledged universal lingua-franca, to communicate in the rapidly-changing globalized world.